New PELOD-2 cut-off score for predicting death in children with sepsis - Ni Made Rini Suari; Abdul Latief; Antonius H. Pudjiadi (Indonesian Pediatric Society, 2021)
Background According to the most recent Sepsis-3 Consensus, the definition of sepsis is life-threatening organ dysfunction caused by dysregulated immune system against infection. Currently, one of the most commonly used prognostic scoring system is pediatric logistic organ damage-2 (PELOD-2) score. Objective To determine and validate the pediatric logistic organ dysfunction-2 (PELOD-2) cut-off score to predict mortality in pediatric sepsis patients. Methods A prospective cohort study was conducted in the intensive care units of Cipto Mangunkusumo Hospital, Jakarta. We assessed subjects with PELOD-2 and calculated the predicted death rate (PDR) using SFAR software. The Hosmer-Lemeshow goodness-of-fit test was used to evaluate calibration and the area under the curve (AUC) of the receiver operating characteristic curve (ROC) to estimate discrimination. Results Of 2,735 children admitted to the emergency department, 52 met the inclusion criteria. Patients had various types of organ dysfunction: 53.8% respiratory, 28.8% neurological, 15.4% cardiovascular, 1.9% hematological. The mortality rate in this study was 38.5%. Mean PELOD-2 score was higher in patients who died than in those who survived [13.9 (SD 4.564) vs. 7.59 (SD 3.025), respectively, P=0.000]. The discrimination of PELOD-2 score with the lactate component had an AUC of 85.5% (95%CI 74.5 to 96.5), while PELOD-2 without lactate had an AUC of 85.4% (95%CI 74.5 to 96.3%). We propose a new PELOD-2 cut-off score to predict organ dysfunction and death of 10, with 75% sensitivity, 72% specificity, 62.5% PPV, and 82% NPV. PELOD-2 score > 10 had a moderate, statistically significant correlation to mortality (r=0.599; P<0.001). Conclusion A PELOD-2 score > 10 is valid for predicting life-threatening organ dysfunction in pediatric patients with sepsis.